Ergonomic risk: social representations of dental students - Luana Kelle Batista Moura; Yara Teresinha Correa Silva Sousa; Guilherme César Batista Moura; Francisca Tereza Coelho Matos; Carlos Alberto Monteiro Falcão; Thiago LIma Monte (Revista de Pesquisa Cuidado é Fundamental Online)
Objective: To learn the social representations of ergonomic risk prepared ​​by dental students. Methodology: This exploratory study, subsidized the Theory of Social Representations, with 64 dental students of an educational institution, by means of interviews. The data were processed in Alceste4.8 and lexical analysis done by the descending hierarchical classification. Results: In two categories: knowledge about exposure to ergonomic risk end attitude of students on preventing and treating injuries caused by repetitive motion. For students, the ergonomic risk is related to the attitude in the dental office. Conclusion: Prevention of ergonomic risk for dental students has not been incorporated as a set of necessary measures for their health and the patients, to prevent ergonomic hazards that can result in harm to the patient caused by work-related musculoskeletal disorder, which is reflected in a lower quality practice.